Effect of Depth and Duration of Cooling on Deaths in the NICU Among Neonates With Hypoxic Ischemic Encephalopathy. Issue 4 (April 2015) - Shankaran, Seetha; Laptook, Abbot R.; Pappas, Athina; McDonald, Scott. A.; Das, Abhik; Tyson, Jon E.; Poindexter, Brenda B.; Schibler, Kurt; Bell, Edward F.; Heyne, Roy J.; Pedroza, Claudia; Bara, Rebecca; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT Hypoxic ischemic encephalopathy (HIE) due to acute perinatal asphyxia is 1 cause of childhood neurodevelopmental deficits among term infants. Induced hypothermia can decrease death or disability, but rates of death or disability remain at 44% to 55%. This multicenter randomized clinical trial among infants with moderate or severe HIE was performed to evaluate the safety and effectiveness of deeper cooling, longer cooling, or both. Neonates were 36 weeks' gestation or greater and admitted to the neonatal intensive care unit (NICU) within 6 hours of birth with poor respiratory effort, need for resuscitation, or diagnosis of encephalopathy. Neonates were stratified into 4 groups: 33.5°C for 72 hours, 32.0°C for 72 hours, 33.5°C for 120 hours, and 32.0°C for 120 hours. The primary outcome was death or disability at 18 to 22 months. Secondary outcomes were deaths in the NICU, number of neonates with support withdrawn, frequency of adverse events, and clinical seizures. Patient accrual was paused after 50 neonates were enrolled and evaluated for the presence of thrombosis or hemorrhage. After every subsequent 25 neonates were enrolled, similar reviews were performed. When 364 neonates were enrolled (of 726 planned), the trial was closed because of emerging safety profile and futility analyses. Of these 364 neonates, 185, 179, 191, and 173 were in the 72-hour, 120-hour, 33.5°C, and 32.0°C groups, respectively. Baseline maternal and neonatal characteristics were generally similar in the 4 groups. Neonatal intensive care unit mortality rates were 7% (7/95 neonates) for the 33.5°C/72-hour group, 14% (13/90 neonates) for the 32.0°C/72-hour group, 16% (15/96 neonates) for the 33.5°C/120-hour group, and 17% (14/83 neonates) for the 32.0°C/120-hour group. Causes of death for neonates in the 33.5°C/72-hour group were asphyxia brain injury in 5, persistent pulmonary hypertension in 1, and other causes in 1. Causes of death in the 32.0°C/72-hour group were asphyxia brain injury in 7, multiorgan failure in 2, sepsis in 1, and other in 3. In the 33.5°C/120-hour group, causes of death were asphyxia brain injury in 7 neonates, multiorgan failure in 6, and persistent pulmonary hypertension and other in 1 each; and for the 32.0°C/120-hour group, asphyxia brain injury in 5, multiorgan failure in 4, persistent pulmonary hypertension in 1, pneumonia in 1, and other in 3. Among neonates with moderate HIE, death in the NICU occurred in 6 (4%) of 144 neonates in the 72-hour group, 11 (8%) of 136 in the 120-hour group, 10 (7%) of 152 in the 33.5°C group, and 7 (5%) of 128 in the 32.0°C group. Among neonates with severe HIE, NICU deaths occurred in 14 (34%) of 41, 18 (42%) of 43, 12 (31%) of 39, and 20 (44%) of 45 in the 4 groups, respectively. The NICU mortality rates for the 120- and 72-hour groups were 16% and 11%, respectively (P = 0.12); rates were 16% and 12% for 32.0°C and 33.5°C groups, respectively (P = 0.47). The adjusted risk ratio for NICU mortality for the 120-hour versus the 72-hour group was 1.37 (95% confidence interval, 0.92-2.04), and for the 32.0°C versus 33.5°C group, 1.24 (95% confidence interval, 0.69-2.25). Safety events were similar in the 4 groups, except the frequency of major bleeding was 3% the 72-hour group compared with 1% in the 120-hour group (P = 0.04). Hospital stays were 26.4 ± 34.1 days and 21.6 ± 15.3 days for the 120- and 72-hour groups, respectively (P = 0.002). In the 32.0°C and 35.5°C groups, respectively, the incidence of bradycardia was 23% versus 1% ( P < 0.001), inhaled nitric oxide 34% versus 24% (P = 0.03), extracorporeal membrane oxygenation 9% versus 4% (P = 0.005), and oxygen for 8.8 ± 8.5 days versus 8.0 ± 9.7 days (P = 0.02) . Hypothermia for 72 hours to a depth of 33.0°C to 34.0°C is usual care for full-term neonates with HIE. Deeper cooling or longer cooling duration compared with hypothermia at 33.5°C for 72 hours did not reduce NICU deaths. The trial was closed because of safety and futility concerns, but primary outcome evaluations of this trial are ongoing. These results have implications for patient care and the design of future trials.